THE IMPLEMENTATION OF EMPLOYEE WORK CULTURE STRATEGY THROUGH THE USE OF ARTIFICIAL INTELLIGENCE IN THE RECRUITMENT PROCESS IN MANUFACTURING COMPANIES - Khaeruman, Khaeruman; Dewi, Irma Nurmala; Faisal, Muhammad (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to examine the implementation of employee work culture strategies through the use of Artificial Intelligence (AI) in the recruitment process in Indonesian manufacturing companies. The use of AI in the recruitment process is seen as an essential innovation to improve efficiency, objectivity, and speed of employee selection. The data for this study was collected through interviews, observations, and documentation in manufacturing companies from October to December 2024, utilising a qualitative approach. The study's findings indicate that AI has the capacity to expedite the selection process, enhance the precision of candidate selection, and positively influence the work culture of new employees by fostering increased discipline and motivation. However, there are challenges in the form of reduced social interaction that affect the cultural adaptation process. The main supporting factors are technological readiness and HR training, while employee resistance and limited data are obstacles that need to be managed strategically. The integration of AI with a humanistic work culture development strategy is recommended in this study to ensure the effective and sustainable execution of digital transformation. These findings contribute to the development of human resource management in the industrial era 4.0, especially in the context of manufacturing companies in Indonesia